Monitoring of the spring waters and geochemistry of ashes leachates during the eruptive crisis (2006) of the Ubinas volcano, Peru - Cruz Pauccara, Vicentina (2007)
Póster (12 P-51) presentado en Cities on Volcanoes 5 conference : Shimabara, Japan, November 19-23, 2007.